(untitled) (Medical Forum Monthly, 2021)
Objective: To determine the frequency of Vitamin B12 deficiency in Gestational Diabetes mellitus (GDM) patients reporting at a tertiary care hospital. Study Design: Observational Study Place and Duration of Study: This study was conducted at the Department of Biochemistry, Gynecology & Obstetrics Liaquat University Hospital Jamshoro from Jan 2018 to December 2018. Materials and Methods: A sample of 291 pregnant women grouped as; 216 diagnosed GDM cases and 75 controls was selected according to criteria. Fasting blood glucose ≥100 mg/dl was taken as GDM. Venous blood samples were centrifuged to separate sera used for the estimation of blood glucose (hexokinase method) and Vitamin B12 (ECLIA assay method). Statistical SPSS software 22.0 (IBM, Inc USA) analyzed data using Student t-test and Chi-square test at 95% CI (P ≤ 0.05). Results: Age (mean±SD) of control and cases was 37.9± 9.51 and 36.3±9.42 years respectively (P=0.81). Vitamin B12 of control and cases was 215.6±43.7 and 155.1±80.7 ng/mL (P=0.0001). Vitamin B12 deficiency was noted in 70.39% of GDM cases compared to 51.6% in controls (P=0.0001). Vitamin B12 shows negative correlation with FBG (r= - 0.176, P=0.031) and RBG (r= - 0.230, P=0.0001). Conclusion: The present study reports 70.39% frequency of vitamin B12 deficiency in gestational diabetes mellitus compared to 51.6% in controls.